2010
DOI: 10.1007/bf03326155
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of different azo dyes by Phanerochaete chrysosporium RP78 under optimal condition

Abstract: ABSTRACT:Detoxification of synthetic dyes is one of the main challenges in clearing textile industry wastes.Biodegradation of azo-dyes using Phanerochaete chrysosporium is one the most environmentally friendly methods available. The main enzymes responsible for mycodecolorization process are lignin and manganese peroxidases. Here, optimization of expression conditions has been carried out with manipulating culture condition and nutrient sources. Therefore, the effects of buffer and temperature as well as nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…By using response surface OPEN ACCESS methodology, the optimal conditions for chromate reduction and dye decolorization were found to be 0.24 g/L glucose, 3.0 g/L (NH 4 ) 2 SO 4 and 0.2 g/L peptone at pH 7 and 35 °C. Ghasemi and colleagues (2010) studied the decolorization of different azo dyes by Phanerochaete chrysosporium RP 78 under optimized conditions [2]. Experimental results showed that the decolorization of azo dyes was due to an enzymatic degradation and 100% decolorization was achieved after 24 hours of reaction.…”
Section: Biological Treatmentmentioning
confidence: 99%
“…By using response surface OPEN ACCESS methodology, the optimal conditions for chromate reduction and dye decolorization were found to be 0.24 g/L glucose, 3.0 g/L (NH 4 ) 2 SO 4 and 0.2 g/L peptone at pH 7 and 35 °C. Ghasemi and colleagues (2010) studied the decolorization of different azo dyes by Phanerochaete chrysosporium RP 78 under optimized conditions [2]. Experimental results showed that the decolorization of azo dyes was due to an enzymatic degradation and 100% decolorization was achieved after 24 hours of reaction.…”
Section: Biological Treatmentmentioning
confidence: 99%
“…Enzymes can act on specific recalcitrant pollutants to remove them by precipitation or transformation to other products. Amongst oxidoreductive enzymes that are involved in dye decolorization, peroxidases such as horseradish peroxidase (HRP), citochrome C peroxidase isolated from yeast, chloroperoxidase isolated from Caldariomyces fumago , several fungal lignin peroxidase (LiP) and manganese peroxidase (MnP) such as LiP from Phanerochaete chrysosporium , and soybean peroxidase have been reported as excellent oxidant agents to degrade dyes in the presence of hydrogen peroxide [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, use of biological agents has attracted worldwide attention for the removal of azo-dyes because of being relatively cheaper and environment friendly in nature (Verma and Madamwar, 2003). Investigated agents include bacteria (Hussain et al, 2013;Mahmood et al, 2013;Anwar et al, 2014); algae (Daneshvar et al, 2007); fungi (Casieri et al, 2008;Ghasemi et al, 2010); and actinomycetes (Khehra et al, 2005). Several researchers have reported the potential of various bacterial strains for removal of azo-dyes (Kalme et al, 2007;Hong et al, 2007;Khalid et al, 2012;Hussain et al, 2013;Anwar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%